Ag nanoparticles supported on a resorcinol-phenylenediamine-based covalent organic framework for chemical fixation of CO2 - Chakraborty, Debanjan; Shekhar, Pragalbh; Singh, Himan Dev; Kushwaha, Rinku; Vinod, C. P.; Vaidhyanathan, Ramanathan (Chemistry-An Asian Journal, 2019)
Covalent organic frameworks are a new class of crystalline organic polymers possessing a high surface area and ordered pores. Judicious selection of building blocks leads to strategic heteroatom inclusion into the COF structure. Owing to their high surface area, exceptional stability and molecular tunability, COFs are adopted for various potential applications. The heteroatoms lining in the pores of COF favor synergistic host-guest interaction to enhance a targeted property. In this report, we have synthesized a resorcinol-phenylenediamine-based COF which selectively adsorbs CO2 into its micropores (12 angstrom). The heat of adsorption value (32 kJ mol(-1)) obtained from the virial model at zero-loading of CO2 indicates its favorable interaction with the framework. Furthermore, we have anchored small-sized Ag nanoparticles (approximate to 4-5 nm) on the COF and used the composite for chemical fixation of CO2 to alkylidene cyclic carbonates by reacting with propargyl alcohols under ambient conditions. Ag@COF catalyzes the reaction selectively with an excellent yield of 90 %. Recyclability of the catalyst has been demonstrated up to five consecutive cycles. The post-catalysis characterizations reveal the integrity of the catalyst even after five reaction cycles. This study emphasizes the ability of COF for simultaneous adsorption and chemical fixation of CO2 into corresponding cyclic carbonates.
Keywords: CO2 capture; covalent organic frameworks; cyclic carbonates; Propargyl alcohols; silver nanoparticles

Aqueous-phase differentiation and speciation of Fe3+ and Fe2+ using water-stable photoluminescent lanthanide-based metal-organic framework - Maity, Rahul; Chakraborty, Debanjan; Nandi, Shyamapada; Yadav, Ankit Kumar; Mullangi, Dinesh; Vinod, C. P.; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2019)
Fe2+ is vital to O-2 transportation and photosynthesis regulated by oxidases and reductases. On the other hand, Fe3+ is detrimental due to its irreversible binding to O-2. Hence there is a need for selective identification of Fe3+ from aqueous systems in the presence of Fe2+. However, given their close chemical nature, it is not straightforward to differentiate them. Fe2+ and Fe3+ are typically sensed and differentiated using magnetic measurements, Mossbauer, X-ray absorption spectroscopy, or EXAFS, which are complex and equipment intensive techniques. In comparison, the fluorescence technique is advantageous in terms of time and accessibility. Although readily available lanthanide salts exhibit fluorescence, they are weak, and to serve as an optical probe, their luminescence has to be enhanced via ligand design. Hence we have designed a chromophoric ligand that can covalently bind to lanthanides and enhance its fluorescence intensity, and it binds selectively to Fe3+ through its nitrogen centers. It detects Fe3+ from low concentration (similar to 100 mu M) aqueous solutions, with fast response time (<1 min) and with a detection limit of 3.6 ppm. Importantly, the Fe3+ adsorbed MOF can be readily reactivated for the next cycle by merely washing with an aqueous ascorbic acid solution and can be used for multiple cycles without any appreciable loss in activity. This makes the Ln-MOF an environmentally benign, cost-effective, scalable, and recyclable probe.
Keywords: Fe3+ differentiation and speciation; flexible ligand; fluorescent MOF; iron speciation; Metal-organic framework; water sorption